2000
DOI: 10.1101/gad.854900
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent regulation of cyclin D1 nuclear export and cyclin D1–dependent cellular transformation

Abstract: cell cycle, but how phosphorylation regulates redistribution has not been resolved. For example, phosphorylation of nuclear cyclin D1 could increase its rate of nuclear export relative to nuclear import; alternatively, phosphorylation of cytoplasmic cyclin D1 by GSK-3␤ could inhibit nuclear import. Here, we report that GSK-3␤-dependent phosphorylation promotes cyclin D1 nuclear export by facilitating the association of cyclin D1 with the nuclear exportin CRM1. D1-T286A, a cyclin D1 mutant that cannot be phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
503
2
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(531 citation statements)
references
References 57 publications
21
503
2
5
Order By: Relevance
“…The fourth pattern was represented by those tumours devoid of cyclin D1 (2/36). These data are consistent with the in vitro observations that cyclin D1 can be stringently regulated as a function of subcellular localisation (Alt et al, 2000;Radu et al, 2003) and reveal that distinct localisation patterns are observed in prostate cancer. Previous studies have shown that cyclin D1 activity is strongly influenced by its subcellular localisation (Diehl and Sherr, 1997;Barr and Johnson, 2001;Lin and Gelman, 2002;Balasenthil et al, 2004;Alao et al, 2006;Sumrejkanchanakij et al, 2006).…”
Section: Disparate Localisation Of Cyclin D1 Is Associated With Prostsupporting
confidence: 91%
“…The fourth pattern was represented by those tumours devoid of cyclin D1 (2/36). These data are consistent with the in vitro observations that cyclin D1 can be stringently regulated as a function of subcellular localisation (Alt et al, 2000;Radu et al, 2003) and reveal that distinct localisation patterns are observed in prostate cancer. Previous studies have shown that cyclin D1 activity is strongly influenced by its subcellular localisation (Diehl and Sherr, 1997;Barr and Johnson, 2001;Lin and Gelman, 2002;Balasenthil et al, 2004;Alao et al, 2006;Sumrejkanchanakij et al, 2006).…”
Section: Disparate Localisation Of Cyclin D1 Is Associated With Prostsupporting
confidence: 91%
“…By contrast, these same studies validated the prediction that cyclin D1b is constitutively nuclear in localization (Lu et al, 2003;Solomon et al, 2003). This was a critical observation, as constitutive nuclear localization of cyclin D1 (as achieved through mutation of T286) is known to promote oncogenic transformation (Alt et al, 2000). Strikingly, it was demonstrated that cyclin D1b harbors increased transforming capability (as compared to cyclin D1) (Lu et al, 2003;Solomon et al, 2003), thus indicating that cyclin D1b may serve as a more potent oncogene in human cancers.…”
Section: The Cyclin D1b Variant Proteinmentioning
confidence: 54%
“…Although highly invoked in the literature, there has not been a detailed analysis of the role for the PEST sequence in regulating cyclin D1 protein stability. In contrast, phosphorylation of the T286 residue has been shown to target the cyclin D1 protein for nuclear export and proteasomal degradation (Alt et al, 2000). Indeed, phosphorylationdependent destruction of cyclin D1 provides a critical barometer to prevent overexpression of cyclin D1 resulting from continuous mitogen-dependent cyclin D1 transcription.…”
Section: Cyclin D1 and Cell Cycle Controlmentioning
confidence: 99%
“…The level of cyclin D1 is tightly controlled for the normal progression of cell cycle and its deregulation is linked to the development of cancer (Bartkova et al, 1994a, b;BaniHani et al, 2000). Overexpression of wild-type cyclin D1 is shown to be insufficient in inducing transformation of cells, because nuclear export and subsequent cytoplasmic proteolysis reduce the oncogenic capability of the protein (Quelle et al, 1993;Alt et al, 2000). In contrast, overexpression of cyclin D1-T286A results in tumorigenesis in transgenic mice (Alt et al, 2000;Gladden and Diehl, 2005;Benzeno et al, 2006;Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Activated AKT phosphorylates the serine9 residue of glycogen synthase kinase-3b (GSK3b) to inactivate its kinase activity on the threonine286 residue of cyclin D1. This later blocks the nuclear export and the cytoplasmic cyclin D1 and undergoes proteasomal degradation (Alt et al, 2000). Thus cyclin D1 accumulates in the nucleus as a result of the phosphatidylinositol-3-OH kinase-and AKT-mediated inactivation of GSK3b.…”
Section: Introductionmentioning
confidence: 99%